2017
DOI: 10.14260/jemds/2017/893
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ocular Morbidities Among School Children in a Rural Block of Cachar, Assam

Abstract: BACKGROUNDSchool-age children constitute a particularly vulnerable group, where ocular morbidity including uncorrected refractive error may have a dramatic impact on learning capability and educational potential. Present study was conducted with the objective of estimating the prevalence of ocular morbidity among school children in rural area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…14 Similarly, studies by Binu et al in Kerala, Kumar et al and Mccrann et al found that there is a significant association between increased daily usage of the smartphone and myopia more than 2 hours. [23][24][25] In the present study, there is a significant inverse association between the increase in outdoor activities and myopia. Similarly in a study by Jin et al on the effect of outdoor activity and myopia, he found an association between the increase in outdoor activities prevented the onset and development of myopia.…”
Section: Discussionsupporting
confidence: 48%
“…14 Similarly, studies by Binu et al in Kerala, Kumar et al and Mccrann et al found that there is a significant association between increased daily usage of the smartphone and myopia more than 2 hours. [23][24][25] In the present study, there is a significant inverse association between the increase in outdoor activities and myopia. Similarly in a study by Jin et al on the effect of outdoor activity and myopia, he found an association between the increase in outdoor activities prevented the onset and development of myopia.…”
Section: Discussionsupporting
confidence: 48%